Comparison of diffuse infrared and far-ultraviolet emission in the Large Magellanic Cloud: The data. (15th November 2016) - Saikia, Gautam; Shalima, P.; Gogoi, Rupjyoti; Pathak, Amit
Abstract: Dust scattering is the main source of diffuse emission in the far-ultraviolet (FUV). For several locations in the Large Magellanic Cloud (LMC), Far Ultraviolet Spectroscopic Explorer (FUSE) satellite has observed diffuse radiation in the FUV with intensities ranging from 1000 to 3×10 5 photon units and diffuse fraction between 5% and 20% at 1100 Å. Here, we compare the FUV diffuse emission with the mid-infrared (MIR) and far-infrared (FIR) diffuse emission observed by the Spitzer Space Telescope and the AKARI satellite for the same locations. The intensity ratios in the different MIR and FIR bands for each of the locations will enable us to determine the type of dust contributing to the diffuse emission as well as to derive a more accurate 3D distribution of stars and dust in the region, which in turn may be used to model the observed scattering in the FUV. In this work we present the infrared (IR) data for two different regions in LMC, namely N11 and 30 Doradus. We also present the FUV IR correlation for different infrared bands.